INNOVATIVE METHODS OF TEACHING FOREIGN LANGUAGES - Orolova Shakhzoda Alisher qizi (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
Nowadays, in the world, the demand for effective foreign language education is being more important. Traditional methods of language instruction often fall short in meeting the needs of modern learners, prompting educators to explore innovative teaching strategies. This article examines a range of contemporary approaches that enhance language acquisition, including the integration of technology, gamification, task-based learning, project-based learning, which help to foster students knowledge, collaboration and they make easier children’s or students’ language learning process These methods not only improve linguistic skills but also foster learner motivation, engagement, and cultural competence and By adopting innovative techniques, language educators can create dynamic, student-centered learning environments that respond to diverse learning styles and the evolving demands of global communication.